International Handbook of Educational Evaluation
XVIII, 1060 p.
Keywords: Thomas Kellaghan Educational Research Centre, St. Patrick's College, Dublin, Ireland Daniel L. Stufflebeam The Evaluation Center, Western Michigan University, Ml, USA Lori A. Wingate The Evaluation Center, Western Michigan University, Ml, USA Educational evaluation encompasses a wide array of activities, including student assessment, measurement, testing, program evaluation, school personnel evalua tion, school accreditation, and curriculum evaluation. It occurs at all levels of education systems, from the individual student evaluations carried out by class room teachers, to evaluations of schools and districts, to district-wide program evaluations, to national assessments, to cross-national comparisons of student achievement. As in any area of scholarship and practice, the field is constantly evolving, as a result of advances in theory, methodology, and technology; increasing globalization; emerging needs and pressures; and cross-fertilization from other disciplines. The beginning of a new century would seem an appropriate time to provide a portrait of the current state of the theory and practice of educational evaluation across the globe. It is the purpose of this handbook to attempt to do this, to sketch the international landscape of educational evaluation - its conceptual izations, practice, methodology, and background, and the functions it serves. The book's 43 chapters, grouped in 10 sections, provide detailed accounts of major components of the educational evaluation enterprise. Together, they provide a panoramic view of an evolving field.